PENGARUH KONTEN DIGITAL TERHADAP KEPERCAYAAN PUBLIK PADA KEPOLISIAN DALAM KASUS BEGAL DI KOTA MEDAN - Ainur Nadzirah; Annisa Zulaura; Daffa Aulia Baihaqi; Grace Mutiara Lovian Sinambela; M. Alfarabi Pratama; Putri Nasha Althoof; Parlaungan Gabriel Siahaan (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
The digital era has transformed how society shapes opinion toward law enforcement institutions. In Medan City, viral begal (motorcycle robbery) content on social media triggered massive public criticism toward the police, while public trust in Polri continuously declined throughout 2021–2025. This study examines the influence of digital content on public trust in the police regarding begal cases in Medan Tembung District.The study employed a quantitative associative approach with 100 respondents via purposive sampling. Data were collected using a 1–5 Likert Scale questionnaire and analyzed through simple linear regression, t-test, and independent sample t-test.The findings confirmed that digital content has a significant negative effect on public trust (β = −0.413; R² = 0.684; p < 0.001). A total of 83 percent of respondents fell in the low trust category, and the high-exposure group showed significantly lower trust than the low-exposure group (t = −24.880; p < 0.001). The police must develop a proactive digital communication strategy to restore public trust.